Beyond the Gap : How Countries Can Afford the Infrastructure They Need while Protecting the Planet - Rozenberg, Julie; Fay, Marianne (Washington, DC: World Bank, 2019)
Beyond the Gap: How Countries Can Afford the Infrastructure They Need while Protecting the Planet aims to shift the debate regarding investment needs away from a simple focus on spending more and toward a focus on spending better on the right objectives, using relevant metrics. It does so by offering a careful and systematic approach to estimating the funding needs to close the service gaps in water and sanitation, transportation, electricity, irrigation, and flood protection. Exploring thousands of scenarios, this report finds that funding needs depend on the service goals and policy choices of low- and middle-income countries and could range anywhere from 2 percent to 8 percent of GDP per year by 2030.